Hubungan Karakteristik Ketahanan Pangan Rumah Tangga dengan Kejadian Stunting pada Balita di Wilayah Kerja Kelurahan Naioni Kota Kupang - Arinya D. Rambadeta; Amelya B. Sir; Indriati A. Tedju Hinga (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Household food security is a risk factor for stunting in children under five years of age. Low family income is a risk factor that affects household food security, which also affects young children's eating habits, so that young children's nutritional intake is inadequate and the incidence of stunting increases. The aim of this research is to analyze the relationship between household food security characteristics and the prevalence of stunting in children under five years of age in the Naioni sub-county working area. The type of research is observational analysis with a case-control design. The research was conducted from February to March 2024. The population of this study consisted exclusively of mothers whose infants were and were not stunted. The sample size in this study was 60 samples with a ratio of 1:1, namely a case group with 30 samples and a control group with 30 samples. This research uses a probability sampling technique, namely simple random sampling. The results of the study showed that there was an association between risk factors for food security p=0.004 (OR=5.67), risk factors for family income p=0.004 (OR=5.50) and risk factors for dietary habits p=0.003 (OR)=6 , 00) with the frequency of stunting in young children in the work area of ​​Naioni Village, Kupang City. This study concludes that household food security, family income and infant feeding habits have a significant association and are risk factors for stunting in infants.